Evidence mapping of wasting programs and their impact along the continuum of care in low- and middle-income countries: A rapid review of the research evidence - Touré, Mariama; Becquey, Elodie; Huybregts, Lieven; Diatta, Dieynab; Booth, Andrew; Verstraeten, Roosmarijn (International Food Policy Research Institute, 2021)
Wasting, also known as acute malnutrition, is a major health problem requiring urgent attention in low- and middle-income countries (LMICs). Wasting is defined as low weight-for-height. According to the World Health Organization (WHO), it often indicates a recent and severe weight loss and usually occurs when a person has not had food of adequate quality and/or quantity and/or they have had frequent or prolonged illnesses.